Persepsi Masyarakat Terhadap Perilaku Demonstrasi Mahasiswa Universitas Muhammadiyah Makassar - Muhajir A; Dewi Susanti (Universitas of Muhammadiyah Makassar, 2018)
This study aims to find out how the public perception of the demonstration behavior of unismuh students in Makassar, especially in carrying out demonstrations carried out by unismatic students of Makassar, they carried out their actions in front of the campus, namely in the street area of Sultan Alauddin Makassar, where feeling disturbed especially the Alauddin Sultan road itself is a connecting road between Gowa Regency - Makassar. This research is to find out how the response of the surrounding community is related to the demonstration carried out by unismatic students in Makassar. The type of research that is used alone is a qualitative descriptive research method, by determining the sample through purposive sampling technique by selecting several informants who have criteria that have been determined by researchers. Data collection techniques used are interview techniques, observation, and documentation. The findings of this researcher are people around the unismuh campus of Makassar, where the campus area on the alauddin Sultan road is a point of density of vehicles and the community usually uses the road. public perception of the unismuh demonstration in Makassar. The results of this study indicate that every public perception originating from the resource persons is very disadvantaged in the demonstrations of unismatic students in Makassar, because it severely disrupts their activities and creates road congestion, but many people from the community also suggest that the demonstration be delivered in front the Suldel DPRD office.Keywords : Perception, Community Around Campus, Demonstration Behavior